The Influence of Activity-Based Costing and Just-in-Time on Efficiency Cost Production with Company Size as a Moderation Variable - Fri Medistya Anke Priyono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Study This aiming for test the influence of Activity Based Costing (ABC) and Just in Time (JIT) on Efficiency Cost Production (EBP) with Company Size as variable moderation. In competition, an increasingly growing industry, strict efficiency cost production has become important in increasing the Power competitiveness and profitability of companies. The ABC method is used for allocate cost based on actual activity​ consume source power, while JIT focuses on reducing waste and optimization production through management proper stock​ time. This Research uses is quantitative approach with a regression moderation approach to test the connection between the variables studied. Data obtained from the company manufacturing listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. The results of the study show that ABC and JIT have an effect positive and significant to efficiency cost production. In addition, Company Size strengthens the influence of ABC on efficiency cost production, but no to moderate the influence of JIT. This is show that more ABC implementation effective in the company with a larger scale large, while JIT can apply optimally without​ influenced by size company. Combination implementation of ABC and JIT can become strategic approach​ in increase efficiency cost production and power competition companies in the industry manufacturing.